Set-point filter design for a two-degree-of-freedom fractional control system - Padula, Fabrizio; Visioli, A. (2016)
© 2014 Chinese Association of Automation.This paper focuses on a new approach to design U+0028 possibly fractional U+0029 set-point filters for fractional control systems. After designing a smooth and monotonic desired output signal, the necessary command signal is obtained via fractional input-output inversion. Then, a set-point filter is determined based on the synthesized command signal. The filter is computed by minimizing the 2-norm of the difference between the command signal and the filter step response. The proposed methodology allows the designer to synthesize both integer and fractional set-point filters. The pros and cons of both solutions are discussed in details. This approach is suitable for the design of two degree-of-freedom controllers capable to make the set-point tracking performance almost independent from the feedback part of the controller. Simulation results show the effectiveness of the proposed methodology.